2012
DOI: 10.1080/1478646x.2011.589516
|View full text |Cite
|
Sign up to set email alerts
|

The first pilot demonstration: solar updraft tower power plant in Jordan

Abstract: The high cost of importing heavy fuel oil from neighbouring countries of Jordan stimulated the need to consider renewable energy as an alternative to imported power. The paper describes a systematic experimental study on the pilot solar updraft tower power plant model system. Particular attention is given to measurements of air velocity, temperature, solar radiation and voltage difference. This is the first pilot solar updraft power plant that has been built in Jordan to evaluate such technology in Mutah Area.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 11 publications
0
14
0
Order By: Relevance
“…The work of [2] presents a simplified theory of the solar tower, practical experience, and economy of solar updraft towers. In the work of Al-Dabbas, 2011 [3], the first pilot demonstration of a solar updraft tower power plant in Jordan is presented. The study of [3] is motivated by the high cost of importing heavy fuel oil from neighboring countries of Jordan.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…The work of [2] presents a simplified theory of the solar tower, practical experience, and economy of solar updraft towers. In the work of Al-Dabbas, 2011 [3], the first pilot demonstration of a solar updraft tower power plant in Jordan is presented. The study of [3] is motivated by the high cost of importing heavy fuel oil from neighboring countries of Jordan.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the work of Al-Dabbas, 2011 [3], the first pilot demonstration of a solar updraft tower power plant in Jordan is presented. The study of [3] is motivated by the high cost of importing heavy fuel oil from neighboring countries of Jordan. The work of [3], [4] describes a systematic experimental study on the pilot solar updraft tower power plant model system with particular attention given to measurements of air velocity, temperature, solar radiation and voltage difference.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The work reported that the solar chimney diameter of 8 cm gained the maximum velocity when the ratio of chimney diameter to chimney height was 0.1. The first pilot solar updraft power plant in Jordan was built by Al-Dabbas [29] (2011) and particular attention was given to the measurements of air velocity, temperature, solar radiation and voltage difference.…”
Section: Review On Experimental Workmentioning
confidence: 99%